Effect of insurance-reimbursed inpatient cancer care in Anhui Province: a retrospective study. Issue 1 (October 2019) - Shen, XingRong; Chai, Jing; Xiao, Siyi; Yao, Anqi; Wen, Kehan; Pan, Qiling; Wang, Debin
Abstract: Background: China's Anhui Province has made great efforts reforming its health systems (eg, reimbursement for medical care for major diseases, clinical path management, and dual referrals), but little is known about the effect of these reforms. This study reveals important evidence in this regard using inpatient cancer care as an indicator of the effect of these reforms on health. Methods: The study used descriptive analysis of reimbursement records for inpatient cancer care in Anhui Province from 2013 to 2017, extracted from the New Rural Cooperative Medical System (NRCMS) database, a medical insurance scheme that covers more than 98% of rural residents. Findings: The study extracted 329 901 inpatient cancer care reimbursement records. From 2013 to 2017, overall coverage of NRCMS-reimbursed inpatient cancer care increased by 14·20 times; per 100 000 people, these increases were 2·22 to 78·42 for lung cancer, 9·09 to 55·74 for stomach cancer, 1·33 to 26·74 for oesophageal cancer, and 0·69 to 45·62 for colorectal cancer. The ratio of per case out-of-pocket expense to annual per capita dispensable income was reduced from 0·51 to 0·32 on average, and from 0·49 to 0·36 for lung cancer, 0·53 to 0·31 for stomach cancer, 0·52 to 0·32 for oesophageal cancer, and 1·02 to 0·55 for colorectal cancer. Both overall and cancer-specific inpatient cancer care expenditure increased at first, which was then followed by a decease. The proportion of cost on operation, nursing, and consultation increased from 1·61% to 10·74% in total expense for all inpatient cancer care and a similar trend was observable for all specific cancers. Overall length of stay decreased from 13·36 to 9·55 days. The Gini coefficient of expenses increased from 0·49 to 0·39 for all inpatient cancer care, and changed from 0·43 to 0·35 for lung cancer, 0·53 to 0·43 for stomach cancer, 0·47 to 0·38 for oesophageal cancer, and 0·51 to 0·41 for colorectal cancer. Interpretation: Health reformation in Anhui Province has resulted in a substantial improvement in coverage of NRCMS-reimbursed inpatient cancer care, economic burden due to inpatient cancer care, and service quality, efficiency, and equity. Funding: Natural Science Foundation of China.